Exploring the phototransformation and assessing the in vitro and in silico toxicity of a mixture of pharmaceuticals susceptible to photolysis - Ofrydopoulou, Anna; Evgenidou, Eleni; Nannou, Christina; Vasquez Christodoulou, Marlen; Lambropoulou, Dimitra (My University, 2021)
The present study comprehensively investigates the phototransformation and ecotoxicity of a mixture of twelve pharmaceutically active compounds (PhACs) susceptible to photolysis. Namely, three antibiotics (ciprofloxacin, levofloxacin, moxifloxacin), three antidepressants (bupropion, duloxetine, olanzapine), three anti-inflammatory drugs (diclofenac, ketoprofen, nimesulide), two beta-blockers (propranolol, timolol) and the antihistamine ranitidine were treated under simulated solar irradiation in ultra-pure and river water. A total of 166 different transformation products (TPs) were identified by ultra-high performance liquid chromatography coupled with Orbitrap high resolution mass spectrometry (UHPLC-Orbitrap HRMS), revealing the formation of twelve novel TPs and forty-nine not previously described in photolytic studies. The kinetic profiles of the major TPs resulting from a series of chemical reactions involving hydroxylation, cleavage and oxidation, dehalogenation, decarboxylation, dealkylation and photo substitution have been investigated and the transformation pathways have been suggested. Additionally, an in vitro approach to the toxicity assessment of daphnids was contrasted with ecotoxicity data based on the Ecological Structure Activity Relationships (ECOSAR) software comprising the in silico tool to determine the adverse effects of the whole mixture of photolabile parent compounds and TPs. The results demonstrated that photolysis of the target mixture leads to a decrease of the observed toxicity.
Keywords: Ecotoxicity; HRMS; Pharmaceuticals; Photolysis; Transformation products